TRANSLATION OF HEADLINES - Khudoyberganova Durdona ismail qizi, (Лучшие интеллектуальные исследования, 2023)
Abstract: This article is about the translation of the titles. At the same time, several translation steps and titles and their translation are noted that illuminate this topic. To better understand this translation step, it is necessary to pay attention to the examples given below.